2000
DOI: 10.1111/0026-7902.00075
|View full text |Cite
|
Sign up to set email alerts
|

Cantonese Speakers' Memory for English Sentences with Prosodic Cues

Abstract: The nature and functions of prosody are reviewed, and English and Cantonese are contrasted for this feature of language, as background for two experimental studies. In the experiments, 30 Cantonese speakers with advanced competence in English were tested for their recognition memory of English sentences in which prosody cued meaning contrasts in otherwise identical sentence pairs. The Cantonese speakers' memory for the English sentences based on prosodic information was generally poor, both when the contrastiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 21 publications
6
53
0
1
Order By: Relevance
“…From a memory study done by Saito (1998), he reported that intonation of a sentence might make a contribution to participants' recall performance (see also Pennington & Ellis, 2000). Following to this point and together with our aforementioned subjective experience, we can see that prosodic information may be useful to our recall performance to the verbal information to an extent, simply like to recall a colloquial slogan in advertisement for a brief period of time.…”
Section: Introductionsupporting
confidence: 59%
“…From a memory study done by Saito (1998), he reported that intonation of a sentence might make a contribution to participants' recall performance (see also Pennington & Ellis, 2000). Following to this point and together with our aforementioned subjective experience, we can see that prosodic information may be useful to our recall performance to the verbal information to an extent, simply like to recall a colloquial slogan in advertisement for a brief period of time.…”
Section: Introductionsupporting
confidence: 59%
“…Moreover, the use of communicative tasks that provide communication opportunities for learners by placing them in authentic situations resulted in better performance of the two experimental groups in comparison to the control group that only had to listen and repeat in an audio-lingual way. In this respect, the results confirm previous findings about the positive effects of advocating a communicative component in pronunciation instruction for the development of accuracy in L2 speech (Elliott, 1997 for instance).They do also corroborate previous results of Pennington and Ellis (2000) who demonstrated that raising learners' awareness towards prosodic features of the target language during training improves their interpretation of sentence meaning and also of Fraser (2000) who believes that forming new concepts of the target language while perceiving and producing speech is a key factor for successful phonological acquisition.…”
Section: Discussionsupporting
confidence: 91%
“…Derwing, Munro and Wiebe (1998) find that ESL students who received instruction emphasizing suprasegmentals (primary stress included) "transferred their learning to a spontaneous production" (p.406) and did significantly better in terms of comprehension and fluency. Pennington and Ellis (2000) claim that EFL learners in their study significantly improved their production of primary stress after receiving explicit instruction. Regarding the effectiveness of techniques for nuclear stress teaching.…”
Section: Introductionmentioning
confidence: 92%